Significance of curve of Spee: An orthodontic review - K P Senthil Kumar; S Tamizharasi (Wolters Kluwer Medknow Publications, 2012)
Exaggerated curve of Spee is frequently observed in dental malocclusions with deep overbites. Such excessive curve of Spee alters the muscle imbalance, ultimately leading to the improper functional occlusion. It has been proposed that an imbalance between the anterior and the posterior components of occlusal force can cause the lower incisors to overerupt, the premolars to infraerupt, and the lower molars to be mesially inclined. This altered condition requires specialized skills for the practitioner. It would be useful if we have a thorough knowledge of how and when this curve of Spee develops, so that it will aid us in our treatment. The understanding of why the curve of Spee develops is limited in literature. The purpose of this article is to increase our knowledge regarding the development and its effect on dentition and its treatment in exaggerated cases.